Sarcosenones A–C, highly oxygenated pimarane diterpenoids from an endolichenic fungus Sarcosomataceae sp. Issue 26 (22nd April 2020) - Hou, Xintong; Xu, Yang; Zhu, Shuaiming; Zhang, Yang; Guo, Liangdong; Qiu, Feng; Che, Yongsheng
Abstract : The new highly oxygenated pimarane diterpenoids sarcosenones A–C (1–3 ) were isolated from an endolichenic fungus Sarcosomataceae sp. Compound 1 showed moderate cytotoxicity towards human tumor cells. Abstract : Three new highly oxygenated pimarane diterpenoids, sarcosenones A–C (1–3 ), and the known 9α-hydroxy-1, 8(14), 15-isopimaratrien-3, 7, 11-trione (4 ), were isolated from cultures of an endolichenic fungus Sarcosomataceae sp. Their structures were elucidated based on NMR spectroscopic data and electronic circular dichroism (ECD) calculations. Compound 1 showed moderate cytotoxicity against a small panel of four human tumor cell lines, with IC50 values of 7.5–26.4 μM.